Can you find the Jersey Devil? : an interactive monster hunt - Hoena, B. A. (North Mankato, Minnesota : Capstone Press, 2023)
In this interactive adventure, the reader who wants to be a cryptozoologist follows the clues to find the legendary Jersey Devil, which has been reported in the Jersey Pine Barrens since the eighteenth century. Includes brief notes on other New Jersey legendary creatures and ghosts.
Monster hunter -- The pine barrens -- Leeds Point -- Barnegat Bay -- History of the Jersey Devil.
Includes bibliographical references (page 111).
5.6
3-6
800L
39 choices, 18 endings--Front cover.
Keywords: Jersey Devil (Monster) -- Juvenile fiction; Monsters -- Juvenile fiction; Cryptozoology -- Juvenile fiction; New Jersey -- Juvenile fiction; Plot-your-own stories; Jersey Devil (Monster) -- Fiction; Monsters -- Fiction; Cryptozoology -- Fiction; New Jersey -- Fiction; Monster fiction; Choose-your-own stories